THE RECONSTRUCTION OFMADLIYAH AND IDDAH MAINTENANCE AND MUT'AH IN DIVORCE CASEFOR JUSTICE AND WELFARE - Mustar Mustar; Gunarto Gunarto; Akhmad Khisni (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In 2015, divorce cases reached 457.493 (85,65%) out of 534.164 cases throughout Indonesia, 321.487(60,18%) cases were dominated by contested divorce cases.1 The most dominant factor of divorce in contested divorce cases is no liability (negligence) of husbands to wives, with the implication that wives' rights during marriage and after divorce are abandoned such as madliyah and iddah maintenance and mut'ah which are husbands' duty. Wives that sued husbands are categorized as nusyuz therefore the reception of madliyah and iddah maintenance is deprived, on the other hand, the reasons of divorce are dominated by the abandonment of wives, thus the definition of nusyuz needs to be reexamined, such as the abandonment of wives by husbands (unjust) is categorized as nusyuz or not. Texts or legal norms in the Compilation of Islamic Law only regulates wives' rights of post-divorce (iddah maintenance and mut'ah) ifthedivorce are at husbands' will or talaq divorce byjudges'ex officio (Article 41 letter c of Law No. 1 of 1974), or by counterclaim from wives for madliyah and iddah maintenance and mut'ah on a condition that wives are not nusyuz. The texts or legal norms in KHI for wives who filed for contested divorce are considered nushuz, thereforethey are deprived of their rights on, the latter is caused by no texts in the Compilation of Islamic Law that regulate it so that the contestants either through law power (advocates) as well as personal did not demandformadliyah and iddahmaintenancein their posita or their petition.